The wireless future : an overview of potential outcomes and trends - Snyder, Scott A. (Scott Andrew), 1965- (FT Press Delivers elements., 2010)
"This Element is an excerpt from The new world of wireless: how to compete in the 4G revolution (ISBN: 9780137003792) by Scott Snyder. Practical business scenario planning for wireless breakthroughs that are about to transform the enterprise--and the world!"--Resource description page